Growth of zircon in metacarbonate rocks from Sør Rondane Mountains, East Antractica - M., Satish-Kumar; Kenji, Horie; Ian, S. Williams; Mami, Takehara; Tomokazu, Hokada; Naho, Otsuji (2016)
第7回極域科学シンポジウム:[OG] 地圏 11月29日（火）国立極地研究所 3階 セミナー室 conference object